The Limestone Diagenesis in The Bojongmanik Formation Based on Petrographic Analysis - Yogie Sani; Tri Rani Puji Astuti; Tito Latif Indra (Lembaga Ilmu Pengetahuan Indonesia, 2023)
The Bojongmanik Formation is a deposit belonging to the Banten Block, has an age range from Middle Miocene toearly Pliocene, and is interspersed with sandstone, marl, shale claystone, and limestone (Sudana and Santosa, 1992).The limestone members of the Bojongmanik Formation are limestones containing mollusks with age equivalent to theMiddle Miocene (Efendi, 1998). This research aims to know the microscopic labeling. This diagenetic process workson the limestone in the Bojongmanik Formation to know the stages of diagenesis and the relationship between thediagenetic process and the porosity of the limestone. The method used in this research is petrographic analysis. Basedon the results of research from 15 samples of thin incisions of the Bojongmanik Formation, there are three types oflimestone: packstone limestone, floatstone limestone, and wackestone limestone, which undergo a process ofdiagenetic cementation, dissolution, neomorphism, microbial micritization, and compaction. The depositionalenvironment of the limestone diagenesis of the Bojongmanik Formation is in the marine phreatic, burial, meteoricphreatic, and meteoric vadose environments. The dominant porosity was found to be vuggy and intraparticle types.One factor that influences the process of diagenesis is the formation of secondary porosity in limestone. The lowerporosity value indicates that there is a little dissolving effect. The higher porosity value indicates much dissolving inthe phreatic zone.Keyword: The Bojongmanik Formation, Petrography Analysis, Porosity, Limestone Diagenesis